2016
DOI: 10.1021/acs.biochem.6b00430
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Cholesterol Recognition Amino Acid Consensus Peptide To Inhibit Binding of a Bacterial Toxin to Cholesterol

Abstract: Recognition of and binding to cholesterol on the host cell membrane is an initial step in the mechanism of numerous pathogens, including viruses, bacteria, and bacterial toxins; however, a viable method of inhibiting this interaction has not yet been uncovered. Here, we describe the mechanism by which a cholesterol recognition amino acid consensus peptide interacts with cholesterol and inhibits the activity of a cholesterol-binding bacterial leukotoxin (LtxA). Using a series of biophysical techniques, we have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 79 publications
3
28
2
Order By: Relevance
“…Previously, we found that a cholesterol recognition amino acid consensus (CRAC) motif is present within the hydrophobic domain and is essential for LtxA binding to cholesterol on the host cell plasma membrane and toxicity [ 24 ]. In the present work, this CRAC site was detected in both the intra- and extra-membrane peptides by MS, indicating that this site may be located very close to the membrane interface, consistent with a mechanism suggested by recent work in our lab [ 47 , 48 ], demonstrating that LtxA recognizes cholesterol near the membrane interface.…”
Section: Discussionsupporting
confidence: 92%
“…Previously, we found that a cholesterol recognition amino acid consensus (CRAC) motif is present within the hydrophobic domain and is essential for LtxA binding to cholesterol on the host cell plasma membrane and toxicity [ 24 ]. In the present work, this CRAC site was detected in both the intra- and extra-membrane peptides by MS, indicating that this site may be located very close to the membrane interface, consistent with a mechanism suggested by recent work in our lab [ 47 , 48 ], demonstrating that LtxA recognizes cholesterol near the membrane interface.…”
Section: Discussionsupporting
confidence: 92%
“…In line with previous observation that CyaA can insert into cholesterol depleted membranes 39 , these results suggest that interaction of the toxin with cholesterol is not involved in the initial interaction with the lipid bilayer prior to toxin incorporation into the plasma membrane of target cells. This distinguishes the mechanism of membrane penetration of CyaA from that of other related RTX cytolysins, such as the A. actinomycetemcomitans LtxA and E. coli HlyA, which possess bona fide cholesterol-binding sites and bind cholesterol with high affinity 41 43 , 52 . Three motifs have, indeed, been previously implicated in cholesterol binding to transmembrane proteins, namely CRAC, CARC (inverted CRAC with the consensus sequence R/K-(X)(1–5)-Y/F-(X)(1–5)-L/V) and a cholesterol consensus motif 53 .…”
Section: Discussionmentioning
confidence: 99%
“…Our lab has recently used a peptide based on the CRAC 336 sequence to characterize the interaction of these amino acids with cholesterol. The affinity of this peptide for a series of model membranes containing cholesterol, desmosterol, dihydrocholesterol, or cholesteryl chloride was measured using SPR (Koufos, Chang, Rasti, Krueger, & Brown, 2016). Each of these sterols differs from cholesterol in the structure of their acyl chain, ring structure, or headgroup, respectively.…”
Section: Host Cell Interactionsmentioning
confidence: 99%
“…The initial studies into this interaction revealed that a peptide based on the CRAC 336 motif could inhibit LtxA cytotoxicity in Jn.9 cells (Brown et al, 2013). Subsequent investigations have built upon this finding to design and synthesize a peptide that inhibits LtxA activity by blocking the binding of the toxin with cholesterol, internalization, and cytotoxicity (Brown et al, 2016; Koufos et al, 2016). We demonstrated that the peptide competes with the toxin for potential binding sites, interrupting the interaction of LtxA with cholesterol.…”
Section: Anti‐ltxa Strategiesmentioning
confidence: 99%
See 1 more Smart Citation